L’éducation À La Santé, Facteur De Promotion De L’action Pédagogique Des Établissements Scolaires - Abdelaziz Khennoussi; Abdelkader Chahlaoui (European Scientific Journal, ESJ, 2018)
Health education is an essential dimension of global education, its absence or marginal position in school life affects the quality of educational action in schools, and deprives students of cognitive and psychosocial skills. In addition, the improvement of learning combines the promotion of the wellbeing of the learner and the good relationship with his teacher and his peers. Both of these conditions can be built by health education. These remarks imply the recasting and broadening of the teaching function so that these fields of "education to" health, the environment, citizenship etc ... are integrated into the professional identity of the teacher and the educational director of the school. Therefore, decision-makers must base their institutional and strategic reform choices on the integration of these interdisciplinary fields into the initial training of teachers. In this perspective, we can renovate the school approach; classically articulated around disciplines and refocusing it around social objectives. Thus, we can work for a new school paradigm that stumbles towards the school of promotion of the individual and society, advocated by the strategic vision of reform of the Moroccan education system 2015-2030.